Carlos Benjamin de Lyra e a topologia algébrica no Brasil - Cobra, Thiago Taglialatela Lima [UNESP] (2014)
This work concerns three main areas: the investigation of the early research on Algebraic Topology in Brazil, the life of the educator and researcher Carlos Benjamin de Lyra (1927 - 1974), and his academic legacy. Initially, we present the beginning of Topology in the world. Next, we present the beginning of research on algebraic topology in Brazil. To this end, we show a brief history of Mathematics course in the creation of the Faculdade de Filosofia, Ciências e Letras of the Universidade de São Paulo (USP). In this context, we point out the relevant work of Lyra in this University and his contribution to the beginning of research in algebraic topology in Brazil, besides the scientific influence exerted over students of his day. We present a biography of Lyra including details about his life, which is changed by trips abroad and what led him to choose Mathematics and subsequently the Algebraic Topology as a field of work. Finally, we make a commented analysis of his work “Introdução à Topologia Algébrica”, which served as a text book for a course taught by him in the “Primeiro Colóquio Brasileiro de Matemática”, in 1957